Zawartość makro- i mikroskładników w glebach poboczy dróg przebiegających przez tereny rolnicze w okresie jesiennym = The content of macro- and microelements in soils of roadsides of roads running through agricultural area in autumn - Iżewska, Anna; Chudecka, Justyna; Tomaszewicz, Tomasz; Wróbel, Mariola (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The authors investigated the content of macro-and microelements soluble in 0.5M HCl in soils of roadsides of roads running through agricultural area of Szczecin Lowland in autumn. Within the roadsides, with a total width of 5 m, separated five zones (A-E) in the system of increasing distances from the edge of roads. The aim of study was to assess of nutrients availability for plants. It was found that the abundance of investigated soils in phosphorus and magnesium was low and very low.
Keywords: pobocza dróg; zawartość makro- i mikroskładników w glebie; roadsides of roads; content of macro- and microelements in soil